Юань гүрний уналтын талаарх өрнөдийн зарим түүхчдийн үзэл - Баттөр, Ж. (Historia Mongolarum, 2008)
Энэхүү өгүүлэлд судлаач Юань гүрний мөхлийн талаархи Өрнөдийн зарим судлаачдын үзлийг задлан авч үзсэн байна. Тэдгээрийн дунд булчирхайн тахал, үерийн гамшиг, Юаний Алтан ургийнхны цус ойртсоноос болсон төр удирдахуйн хямрал, Монголын цэрэг арми Хятадад суурьшсан болон үе залгамжлах ёс зэргээс үүссэн давуу байдлын алдралууд гэхчилэн өвөрмөц хариултуудыг тоочсон байна. Ингэхдээ Монголын түүхийн онцгой чухал сурвалжуудаар зарим санааг нь батжуулсан байна. Өрнөдийн зарим түүхчдийн үзэл тухайлбал, хонины мах идэх юм уу, архи их ууснаас болж монголчуудын хүч доройтсон гэх мэт үзлийг шүүмжлэв. Ерөнхийдөө Өрнөдийн түүхчдийн дэвшүүлсэн, нотолсон олон санаа нь Монголын түүхийн энэ үеийг тайлбарлахад чухал ач холбогдолтой гэж үзэж байнаа In this article, the author analyzed some of the Western historians views on the decline and collapse of the Yuan dynasty In doing so, the author aimed at avoiding the explanations on the decline of Yuan dynasty through the traditional Marxist approaches, like theory of the class struggle, feudal exploitation or social revo)u ions etc, but at revealing some hidden internal social factors from the writings of Western historians. They tried to find the main reasons of decline of Yuan dynasty in such original and incredible factors, including bubonic plague, flood disaster, crisis in ruling administration methods, consanguinity and inbreeding in the relatives in the ruling family, hereditary military household system of Mongolian army, ill fated changes in nomadic Mongolians arisen from in Chinese new environment etc,. The author tried to add some proofs to their findings in Mongolian, Chinese and Persian historical sources. Also he criticized the opinions of the Western historians who argued that Mongolian Empire collapsed because of too much mutton consumption or wide spread alcoholism In general, many ideas of Western historians are very important to understand many mysterious phenomena of this extraordinary and turbulent period of the Mongolian history.